SIMULATION AND PERFORMANCE ANALYSIS OF A HYBRID ROCKET ENGINE WITH SELF-PRESSURIZING OXIDIZER - Costa, B. P.; Goulart, A. C.; Yamato, G. L.; Silva, J. P. V. B.; Fontoura, I. S.; Cruz, M. A. C.; Paula, M. B.; Capacia, V. N. (Revista de Engenharia Térmica, 2022)
There are many challenges to simulate and design a hybrid engine, such as the dimensioning of the feed lines and tanks, propulsive performance calculations, and simulations of the expected behavior in the combustion chamber and the oxidizer tank during the engine operation. In this work, methods are assembled in a concise and complete analysis of the Gluon hybrid rocket engine, developed by PION Labs, with a blowdown pressurization system, using N2O as oxidizer and a paraffin-based fuel. For that, a study will be presented on the peculiar characteristics of the oxidizer and its behavior during the phases of operation of the rocket engine. Then, the main equations that describe the operation of the rocket engine, including the combustion chamber, injection plate, feed lines, and the oxidizer tank are presented, and the performance indicators calculations of the engine are shown and discussed. Finally, simulation results of the combustion chamber and the oxidizer tank during engine firing will be presented, leading to the concluding remarks on the data obtained.